Interior design as a factor for enhancing restaurant experiences of college students in restaurants located along Maginhawa St. a multiple case study - Angeles, Miguel Ramon R. Jr (College of Home Economics, University of the Philippines Diliman, 2019)
This study primarily deals with determining whether interior design could be considered as a factor for enhancing restaurant experiences for college students in restaurants located along Maginhawa Street. In addition, the researcher aimed to find out to what degree interior design affects the experience of college students in the aforementioned restaurants. The researcher utilized the Theory of Fourth Dimension to guide the data analysis for the study. Prior to data gathering, the researcher hypothesized that interior design could be considered as a factor that affects a college student's experience in a restaurant, however, several other factors such as food and service quality could be considered as intervening variables. The researcher used a multiple case study approach for the study, utilizing three cases.. Three restaurants were chosen using a purposive sampling approach, with the main criterion being that the restaurants must be located along Maginhawa Street. The researcher then employed the use of three focus group discussions with composed of three to five college students per focus group discussion. The participants were chosen through purposive sampling, with the criteria for participation being a student currently enrolled in any undergraduate course except for BS Architecture and BS Interior Design. Interviews with the owners of the three selected restaurants were also conducted, as well as personal observation as the methods of data gathering. The results of the study showed a direct relationship between the design intention, design translation and reception of the customers, suggesting that all three must be consistent in order for the customers to have a better restaurant experience. In conclusion, the restaurant must be designed in a way that appeals to the "reality levels", which shape the way each person experiences a space, of the intended target market in order to limit the amount of dissatisfied customers with their restaurant experience.